Evaluation of material properties of cultural heritage building by destructive and non- destructive testing: Malatya Tas,horan Church case study - Ozmen, Alper; Sayin, Erkut (Elsevier Sci Ltd, 2023)
Historical masonry structures are an essential component of cultural heritage. These structures may transfer the lifestyle of previous civilizations to next generations. In order to prevent earthquake damage to these structures, it is important to obtain accurate information on their material properties for reliable computational modelling and strengthening intervention programs. In this context, Destructive Techniques (DT) and Non-Destructive Techniques (NDT) were used together and the results obtained were compared. Tas,horan Church located in Malatya, Turkey was selected as a case study. The aim of this study is to compare the obtained results of Destructive Techniques (DT) and Non-Destructive Techniques (NDT) used to evaluate the original and restoration stones of Tas,horan Church in Malatya, Turkey. The tests conducted include uniaxial compressive strength, flexural strength, water absorption, density, porosity, XRD, SEM-EDX and ageing tests with different solutions (5% H2SO4, 5% HCl and %14 Na2SO4). In addition, NDT methods such as Schmidt hardness, ultrasonic pulse velocity and infrared thermography were used to determine dynamic Poisson's ratio, dynamic modulus of elasticity and UCS. NDT and DT values of the original and restoration stones were presented.
Keywords: Non-destructive testing; Historical masonry buildings; Natural building stones; Destructive testing; Infrared Thermography